Design optimization, construction and testing of 2 K Joule-Thomson heat exchanger for a superfluid helium cryogenic system. (5th November 2020) - Han, Ruixiong; Zou, Zhengping; Ge, Rui; Chang, Zhengze; Zhang, Jianqin; Xu, Miaofu; Ye, Rui; Zhu, Keyu; Zhang, Lei; Zhao, Tongxian; Sun, Liangrui; Zhang, Xiangzhen; et al.
Highlights: Heat transfer performances of the HFHE are investigated by a finite difference analysis method. The influences of the geometrical parameters on the performances are investigated. The theoretical calculation of the HFHE is verified by the experiments in the SHCS. Abstract: The performances of 2 K Joule–Thomson (J-T) heat exchanger are related to the operation efficiency and economy of the superfluid helium cryogenic system, and the helically finned-tube heat exchanger (HFHE) is designed and tested. Heat transfer characteristics of the HFHE are investigated by a finite difference analysis method, and the design optimization of the HFHE is performed by the orthogonal test and variance analysis method. Meanwhile, the influences of the geometrical parameters on the performances are discussed. The experimental investigation of the HFHE is carried out in the superfluid helium cryogenic system, and the performances of the HFHE are verified experimentally. The results are shown that the calculated performances of the HFHE cause by heat transfer are in reasonable agreement with the experimental results, which indicates that the thermal calculation model of the HFHE is more accurate. Moreover, the deviations of pressure drop of cold fluid between the calculation and measurement are analyzed and the friction factor is modified in this paper.